Electronic Properties of Synthetic Shrimp Pathogens-derived DNA Schottky Diodes - Rizan, Nastaran; Chan, Yen Yew; Niknam, Maryam Rajabpour; Krishnasamy, Jegenathan; Bhassu, Subha; Goh, Zee Hong; Devadas, Sridevi; Din, Mohamed Shariff Mohd; Tajuddin, Hairul Anuar; Othman, Rofina Yasmin; Phang, Siew Moi; Iwamoto, M.; et al. (Nature Publishing Group, 2018)
The exciting discovery of the semiconducting-like properties of deoxyribonucleic acid (DNA) and its potential applications in molecular genetics and diagnostics in recent times has resulted in a paradigm shift in biophysics research. Recent studies in our laboratory provide a platform towards detecting charge transfer mechanism and understanding the electronic properties of DNA based on the sequence-specific electronic response, which can be applied as an alternative to identify or detect DNA. In this study, we demonstrate a novel method for identification of DNA from different shrimp viruses and bacteria using electronic properties of DNA obtained from both negative and positive bias regions in current-voltage (I-V) profiles. Characteristic electronic properties were calculated and used for quantification and further understanding in the identification process. Aquaculture in shrimp industry is a fast-growing food sector throughout the world. However, shrimp culture in many Asian countries faced a huge economic loss due to disease outbreaks. Scientists have been using specific established methods for detecting shrimp infection, but those methods do have their significant drawbacks due to many inherent factors. As such, we believe that this simple, rapid, sensitive and cost-effective tool can be used for detection and identification of DNA from different shrimp viruses and bacteria.